Prevalence of Helmet Use among Motorcycle Riders in Bangyai District, Nonthaburi - Siriprakob, Chanya; Kitsanapun, Apaporn; Changchivong, Suratchana (Journal of Health Science of Thailand, 2017)
The purpose this survey research was to assess the situation of helmet use and to determine the relationship between helmet wearing and the type of road among motorcycle riders in Bangyai District, Nonthaburi Province, Thailand. The total of sample size was 360 motorcycle riders selected by accidental sampling. Data were collected by a structured observational checklist; and were analyzed by frequency, percentage, odd ratio and multiple logistic regression. It was found that the prevalence helmet use among motorcycle riders in Bangyai district Nonthaburi was 62.12%. Riding on the highways and rural roads was found to be significantly associated with higher proportion of helmet wearing (OR=15.74; 95%CI=6.48– 38.27 and OR=3.01; 95%CI=1.21–7.47, respectively). Another findings was that clear sky was sig-nificantly associated with the helmet wearing (OR=0.28; 95%CI=0.14–0.56). After control the influ-ence of the clear sky variable, riding on highways and rural roads were significantly associated with helmets use among motorcycle riders (OR=17.05; 95%CI=6.39–45.54 and OR=3.00; 95%CI=1.18– 7.67, respectively).